1992
DOI: 10.1021/es00034a015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and kinetics of autoxidation of calcium sulfite slurries

Abstract: The kinetics of Co-catalyzed autoxidation of calcium sulfite was studied to deepen knowledge of the mechanism of this chain reaction. Laboratory experiments were performed under heterogeneous conditions using two different reactors: a stirred tank with a plane gas-liquid (slurry) interface and an impinger. The reaction course was followed by monitoring the conductivity of the reacting solution and by quenching with iodine solution, respectively. Mechanistic judgments were derived from the influence of sulfite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Moreover, it has been reported that deprotonated complexes (Co(II)−OH), which is more reactive toward SO 3 2− compared to HSO 3 − would be formed at alkaline pH values (R1) leading to the formation of a Co(II)−SO 3 complex [27]. Co(II)−SO 3 could be oxidized to Co(III)−SO 3 + complex in the presence of dissolved oxygen as reported in different works (R2 and R3) [38]. SO 3 − could be generated during the redox reaction between the Co(III)-SO 3 + complex and SO 3 2− (R4).…”
Section: Effect Of Initial Ph On Paracetamol Degradationmentioning
confidence: 97%
“…Moreover, it has been reported that deprotonated complexes (Co(II)−OH), which is more reactive toward SO 3 2− compared to HSO 3 − would be formed at alkaline pH values (R1) leading to the formation of a Co(II)−SO 3 complex [27]. Co(II)−SO 3 could be oxidized to Co(III)−SO 3 + complex in the presence of dissolved oxygen as reported in different works (R2 and R3) [38]. SO 3 − could be generated during the redox reaction between the Co(III)-SO 3 + complex and SO 3 2− (R4).…”
Section: Effect Of Initial Ph On Paracetamol Degradationmentioning
confidence: 97%
“…Compared of Mg 2+ with 2S 2 2P 6 outmost electron configurations, the Co 2+ with 3d 7 electron configurations could accommodate the electron delocalized away from SO 3 2– , resulting a electron hole in SO 3 2– . Thus the free radicals of ·SO 3 – are produced that initiate the chain reaction as follows. , .25ex2ex chain initiation SO 3 2 + Co 2 + SO 3 + Co + (1) chain propagation SO 3 + normalO 2 SO 5 (2) SO 5 + SO 3 2 SO 5 2 + SO 3 (3) product formation SO 5 2 + SO 3 2 2 SO 4 2 (4) chain termination SO …”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we assumed that eq was the slowest step, and eq is also slow, which was considered by Ba̅ckstro̅m in his well-known mechanism of this chain reaction. Thus, the production rate of •SO 3 – is expressed as k 1 × [HSO 3 – ] × [O 2 ], where k 3 × [•SO 5 – ] × [SO 3 2– ] is much less and neglected. Hence, the extinction rate of •SO 3 – is expressed as k 5 × [C 2 H 5 OH] × [•SO 3 – ] 2 , where k 2 × [•SO 3 – ] × [O 2 ] is much less and neglected.…”
Section: Discussionmentioning
confidence: 99%